A Monetary Impulse Measure for Medium-Term Policy Analysis - McCallum, Bennett (IMF Working Papers; Working Paper ;, 1994)
The paper presents a measure of monetary impulse that is intended to reflect the medium-term inflationary implications of a nation's current monetary policy. The measure consists of the growth rate of the monetary base, adjusted for reserve requirement changes and augmented by an implicit forecast of future growth rates of base velocity. Time series plots of the impulse measure for the G-7 countries are presented, and are compared with plots of inflation and of two alternative monetary indicators-the yield curve slope and the growth rate of a broad monetary aggregate. The impulse measure serves well as a medium-term indicator of future inflation, and on balance matches or outperforms the alternative indicators.